Path Span in VANETs Using Position Based Routing Protocol - R, Sharma; P, Garg; A, Rani (International Journal of Engineering and Technology, 2018)
Vanets (Vehicular Ad-hoc Networks) are the minor-class systems of Manets (Mobile Ad-Hoc Networks) or it can beÂ created using Manets. In which there is no access point Vanets are subclass systems of Manets in this no access point to say every node those are inÂ high mobility collect andÂ accept the incoming data in the network. The network density is infrequent in MANET while in VANETs it is dense and frequent. VANETS plays an important role in context of safety ofÂ moving vehicles that includes Infringement Warning, FallÂ Â back direction information, Electronic constraint warning, Collision monitory, etc. Change inÂ network topology due to Mobility of vehicle affectsÂ throughput and efficiency, that results the failure of link on the routeÂ between source and destination. The span of track is rely on the designing of routing rules of conduct.. The evaluation of the track span is count on the knowledge of the entire network topology that changes frequently due to huge motility of the automobiles. Therefore, the estimation of the Path span in the VANETs can reduce the communication and the route maintenance overhead.Â In this, benefaction is a probabilistic and mathematical perusal of Path span in VANET, based on position-based routing concept. We will attain the probability distribution as expectedÂ Route from source to destination in VANET, using position-based routing protocol We willÂ presume that vehicles have not reaches the speed limit, and not stopped. We will analyze result for the estimation of Path span between source and destination in VANETs with the help of Proposed Mathematical Model.Â Â